Peran Disiplin Kerja Memediasi Pengaruh Iklim Organisasi terhadap Kepuasan Kerja Pegawai Dinas Pariwisata Kabupaten Badung - Ida Ayu Gayatri Putri Kaleran; Ni Wayan Mujiati (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
Human resource management in government agencies considers employees as operational factors that contribute to the success and efficiency of public service delivery, so it is necessary for government agencies to maintain employee job satisfaction. This study aims to analyze the role of work discipline in mediating the effect of organizational climate on job satisfaction of Badung Regency Tourism Office employees. This study used a sample of 94 people using the saturated sample technique method. Data collection is done through observation, interviews, and surveys. The data collected was then analyzed using path analysis techniques, classical assumption tests, Sobel tests, and Variance Accounted For (VAF) tests. The results showed that organizational climate has a positive and significant effect on job satisfaction. Organizational climate has a positive and significant effect on work discipline. Work discipline has a positive and significant effect on job satisfaction. Work discipline partially mediates the effect of organizational climate on job satisfaction. The results of this study can contribute to the two-factor theory and be taken into consideration by the Badung Regency Tourism Office in increasing employee job satisfaction.